(untitled) (Al-Academy, 2021)
The twentieth century witnessed developments, transformations and artistic revolutions, including what was witnessed in Arab art, especially contemporary Iraqi plastic art, and as a result, research and studies have increased that dealt with its topics in different ways, which has become a presence that gave it its own language and unique discourse, especially the body, thus opening the way for its employment in composition, to become a form. It denotes interpretable meanings through its various formal representations, which are artistic, cultural and cognitive products. The modernity of the Iraqi formation in the body has passed through different roles, so it started to deal with the body as a representation that reflects the real environment as it is without change. Many artists drew people’s faces (portraiture) and in different social scenes and nature.The importance of the research lies in explaining the mechanisms of the representations of the body with its artistic, intellectual and aesthetic manifestations by monitoring its transformations, as it is an important material from the natural, realistic, mythological and symbolic themes that contained it and because it was associated with the interesting human existence. The aim of the research: To identify the representations of the body in the works of the artist Ali Al-Najjar. The limitation of the research: thematically: representations of the body in the drawings of the artist Ali Al-Najjar executed in inks and oil colors. Spatially: Iraq, Sweden, and my time: 1975-2003As for the theoretical framework, in which the study dealt with three topics: The first topic included the first topic: the conceptual and epistemological root of the body, and the second topic: the body in modern art: The third topic: artist Ali Al-Najjar, experience and style, and the most important indicators of the theoretical framework.In addition to the research procedures, it included the research community, the research sample, the research tool, the research method, and then analyzing the samples, results and conclusions reached by the researchers, including:1. The artist used to strip his human bodies in most of his artwork. All of this is done on the desire of the artist to perform it ... based on his own psychological and emotional desires. As in the example (1,2,3).2. His works carried a psychological content, due to the disease that had coexisted with the artist for a long time. This struggle is in declaring and trying to prove his innocence completely, and as a means of expressing a human concern that always occupies his imagination.